2019
DOI: 10.3389/fvets.2019.00130
|View full text |Cite
|
Sign up to set email alerts
|

Sero-Epidemiology of Foot and Mouth Disease in Domestic Ruminants in Amhara Region, Ethiopia

Abstract: This study involved cross-sectional serological and questionnaire-based surveys to investigate the sero-epidemiology of foot and mouth disease (FMD) in domestic ruminants, and farmers' knowledge and practices about the disease in the Amhara region of Ethiopia. A multistage cluster sampling was carried out to select domestic ruminants for serological sampling and for the interview with farmers. A total of 1,672 sera samples were collected and tested using a 3ABC-Enzyme Linked Immunosorbent Assay, and 170 farmer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
31
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 16 publications
14
31
6
Order By: Relevance
“…At individual animal level, caprine (goats) showed higher seroprevalence than ovine (sheep). This is in agreement with the findings by Mesfine et al [33] but in contrast to what has been reported by other researchers who found FMD sero-positivity to be significantly higher in sheep than in goats [38,40,46]. Others found sero-prevalence to be significantly higher in goats than in sheep [35,42].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…At individual animal level, caprine (goats) showed higher seroprevalence than ovine (sheep). This is in agreement with the findings by Mesfine et al [33] but in contrast to what has been reported by other researchers who found FMD sero-positivity to be significantly higher in sheep than in goats [38,40,46]. Others found sero-prevalence to be significantly higher in goats than in sheep [35,42].…”
Section: Discussionsupporting
confidence: 92%
“…In this study the country sero-prevalence of FMD in SR was found to be 23.3% similar to what has been reported in other countries where FMD is endemic [41,42]. It is however higher than that reported in Ethiopia, Israel, Libya and Sudan [33,34,36,37,43] but about half of what has been reported in Tanzania and Myanmar [39,44,45]. A previous study in cattle in Kenya showed much higher sero-prevalence in cattle at 52.5% [70] and unpublished data obtained at the same time with this current study in Kenyan cattle revealed a sero-prevalence rate of 37.6% in cattle.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…Based on data over the years 2007-2012, annual district level incidence of FMD outbreak was estimated at 0.24, 0.39 and 0.85 per district year in the crop livestock mixed, pastoral and market-oriented districts, respectively, and the outbreaks were caused by serotypes O, A, SAT 2 and SAT 1 (Jemberu et al, 2016). Serological studies of FMD undertaken in different parts of the country reported seroprevalence ranging from 5.6% to 24.2% (Desissa, Tura, Mamo, & Rufae, 2014;Jenbere, Etana, & Negussie, 2011;Mekonen, Beyene, Rufael, Feyisa, & Abunna, 2011;Mesfine, Nigatu, Belayneh, & Jemberu, 2019;Mohamoud, Tessema, & Degefu, 2011;Zerabruk, Romha, & Rufael, 2014).…”
Section: Introductionmentioning
confidence: 99%